Indicator 3 of the External Evaluation Model for Accreditation in Ecuador: A Critical Analysis - Ávila, Zulema (Journal of Education Method and Learning Strategy, 2026)
Introduction: The internationalization of higher education has become a strategic process essential for addressing the challenges of a globalized world. This phenomenon, driven by academic mobility, inter-institutional cooperation, and the adoption of international standards, has transformed university management and its core functions. Objective: To critically analyze Indicator 3, “Internationalization and Mobility,” of the 2023 External Evaluation Model for Accreditation by CACES in Ecuador, in relation to its impact and approach to the internationalization process. Methodology: The study followed a qualitative approach through documentary analysis and literature review. Official regulations and scientific articles were collected, prioritizing those published within the last five years. The analysis was structured into three phases: document selection, thematic coding, and theoretical triangulation. Results: Indicator 3 evaluates the planning, implementation, and monitoring of internationalization strategies through academic mobility, institutional agreements, networks, and international accreditations. It acknowledges the presence of a responsible unit and the integration of evaluation processes for continuous improvement. However, its qualitative nature limits inter-institutional comparability and tends to prioritize documentary evidence over transformative outcomes. Conclusion: The model provides a significant foundation for strengthening the quality of higher education in Ecuador. Its qualitative approach emphasizes documentary evidence. While not all institutions may show high levels of mobility or signed agreements, they can demonstrate solid, innovative, and sustainable strategies.